2016
DOI: 10.1186/s40064-016-3314-y
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the right method for hypospadias repair to achieve optimal results for the primary situation

Abstract: Background Over the past two decades, Snodgrass tubularized incised plate (TIP) urethroplasty has become one of the dominant surgical techniques with wide applications and excellent cosmetic results. However, TIP has many limitations. We performed a retrospective study at our department and assessed the outcome of the inlay internal preputial graft for extending the applications of TIP.MethodsBetween January 2009 and December 2013, we performed a retrospective study consisting of approximately 508 primary dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Later, TIP has become mainstream internationally as the optimal surgical option. 5 Any technique to repair distal hypospadias should be simple, easy, and could result in satisfactory functional and cosmetic outcomes. Despite continued refinement of numerous repair techniques, there is no satisfactory technique in terms of complications and cosmesis.…”
Section: Introductionmentioning
confidence: 99%
“…Later, TIP has become mainstream internationally as the optimal surgical option. 5 Any technique to repair distal hypospadias should be simple, easy, and could result in satisfactory functional and cosmetic outcomes. Despite continued refinement of numerous repair techniques, there is no satisfactory technique in terms of complications and cosmesis.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 1753 patients who underwent a primary hypospadias repair, 1334 (76%) were distal and 419 (24%) were proximal. In the intervention group (DIGU), the type of graft was preputial in 12 studies, only one single arm study reported the use of a lingual graft [7] and one NRS study reported a subgroup with buccal mucosal graft [8].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…A total of 5 NRSs (1 prospective [10] and 4 retrospective studies [8,10e13]) including 908 patients met the inclusion criteria. Two of the studies included distal hypospadias only [10,11], one study included proximal hypospadias [12] only and two included both distal and proximal hypospadias [8,13]. All the NRS studies used preputial grafts with the exception of one study with two intervention groups, one of which included a buccal graft [8].…”
Section: Characteristics Of Nrs'smentioning
confidence: 99%
“…However, a limited number of studies have looked in detail the impact of such variables on the postoperative outcomes [5,6]. Preservation of the UP has been considered the landmark for the majority of techniques for distal hypospadias repairs, especially for the tubularized incised plate (TIP) and Thiersch Duplay's urethroplasty, the most frequently utilized procedures [1,7].…”
Section: Introductionmentioning
confidence: 99%